MYTHOLOGY AND SHAMANISM IN SOCIAL RELATIONSHIPS OF THE INUIT AND KAINGANG - Rosa, Rogério Reus Gonçalves da (Espaço Ameríndio, 2011)
From the exchange system established between humans, non-human and superhuman this article will analyze the importance of mythological thinking and shamanism in social relations of the Inuit and Kaingang. The objectives of this paper are analyze the mythology and shamanism; present the mythological narratives about the origin Inuit and Kaingang; observe the implications of mythology and shamanic systems in configurations of sex and gender of men and women living in the central Canadian Arctic and in the lowlands of southern Brazil. A partir do sistema de trocas estabelecido entre humanos, não humanos e super-humanos, este texto assinala a importância do pensamento mitológico e do xamanismo nas relações sociais dos Inuit e dos Kaingang. Os objetivos desse artigo são os seguintes: analisar a mitologia e o xamanismo; apresentar as narrativas mitológicas acerca da origem inuit e kaingang; e, por fim, observar comparativamente as implicações da mitologia e dos sistemas xamânicos nas configurações de sexo e gênero de alguns homens e mulheres que vivem no Ártico central canadense e nas terras baixas do Brasil meridional.